Evaluation of the immunogenicity of the dabigatran reversal agent idarucizumab during Phase I studies. (6th April 2017) - Norris, Stephen; Ramael, Steven; Ikushima, Ippei; Haazen, Wouter; Harada, Akiko; Moschetti, Viktoria; Imazu, Susumu; Reilly, Paul A.; Lang, Benjamin; Stangier, Joachim; Glund, Stephan
Abstract : Aims: Idarucizumab, a humanized monoclonal anti‐dabigatran antibody fragment, is effective in emergency reversal of dabigatran anticoagulation. Pre‐existing and treatment‐emergent anti‐idarucizumab antibodies (antidrug antibodies; ADA) may affect the safety and efficacy of idarucizumab. This analysis characterized the pre‐existing and treatment‐emergent ADA and assessed their impact on the pharmacokinetics and pharmacodynamics (PK/PD) of idarucizumab. Methods: Data were pooled from three Phase I, randomized, double‐blind idarucizumab studies in healthy Caucasian subjects; elderly, renally impaired subjects; and healthy Japanese subjects. In plasma sampled before and after idarucizumab dosing, ADA were detected and titrated using a validated electrochemiluminescence method. ADA epitope specificities were examined using idarucizumab and two structurally related molecules. Idarucizumab PK/PD data were compared for subjects with and without pre‐existing ADA. Results: Pre‐existing ADA were found in 33 out of 283 individuals (11.7%), seven of whom had intermittent ADA. Titres of pre‐existing and treatment‐emergent ADA were low, estimated equivalent to <0.3% of circulating idarucizumab after a 5 g dose. Pre‐existing ADA had no impact on dose‐normalized idarucizumab maximum plasma levels and exposure and, although data were limited, no impact on the reversal of dabigatran‐induced anticoagulation by idarucizumab. Treatment‐emergent ADA were detected in 20 individuals (19 out of 224 treated [8.5%]; 1 out of 59 received placebo [1.7%]) and were transient in ten. The majority had specificity primarily toward the C‐terminus of idarucizumab. There were no adverse events indicative of immunogenic reactions. Conclusion: Pre‐existing and treatment‐emergent ADA were present at extremely low levels relative to the idarucizumab dosage under evaluation. The PK/PD of idarucizumab appeared to be unaffected by the presence of pre‐existing ADA.